The ethical journalist making responsible decisions in the pursuit of news - Foreman, Gene (Chicester, West Sussex Wiley-Blackwell, 2015)
"A new edition of this well-regarded, student-friendly text book for journalism ethics that addresses the challenges of digital-age journalism"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Journalistic ethics; Reporters and reporting; Journalistic ethics -- Case studies; Reporters and reporting -- Case studies